2005
DOI: 10.1002/sce.20070
|View full text |Cite
|
Sign up to set email alerts
|

Guided school visits to natural history museums in Israel: Teachers' roles

Abstract: ABSTRACT:Museums are favorite and respected resources for learning worldwide. In Israel, there are two relatively large science centers and a number of small natural history museums that are visited by thousands of students. Unlike other countries, studying museum visits in Israel only emerges in the last few years. The study focused on the roles and perceptions of teachers, who visited four natural history museums with their classes. The study followed previous studies that aimed at understanding the role tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
24

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 20 publications
1
60
0
24
Order By: Relevance
“…Teachers influence students' understanding and attitudes about science and possible future careers in STEM-related subjects, such as engineering. Through experiences such as field trips, teachers can facilitate the interaction of in-class science learning and experiences with informal design spaces, yet studies have consistently documented that teachers play a small role in the planning and execution of excursions outside of the schoolroom and connecting these field trip experiences to classroom content (Anderson & Zhang, 2003;Griffin & Symington, 1997;Griffin, 1994;Tal, Bamberger, & Morag, 2005). In Griffin's (1994) study, half of the teachers from 13 schools reported that they planned on doing some follow-up activities after their field trip excursions, but only a half of those teachers, a quarter of the sample, actually implemented these follow-up activities.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers influence students' understanding and attitudes about science and possible future careers in STEM-related subjects, such as engineering. Through experiences such as field trips, teachers can facilitate the interaction of in-class science learning and experiences with informal design spaces, yet studies have consistently documented that teachers play a small role in the planning and execution of excursions outside of the schoolroom and connecting these field trip experiences to classroom content (Anderson & Zhang, 2003;Griffin & Symington, 1997;Griffin, 1994;Tal, Bamberger, & Morag, 2005). In Griffin's (1994) study, half of the teachers from 13 schools reported that they planned on doing some follow-up activities after their field trip excursions, but only a half of those teachers, a quarter of the sample, actually implemented these follow-up activities.…”
Section: Discussionmentioning
confidence: 99%
“…Çünkü yapılan çalışmalarda iyi planlanmış ve okul müfredatıyla iyi ilişkilendirilmiş alan gezilerinin başarılı sonuçlar vereceği vurgulanmıştır (Bowker & Tearle, 2007;Kisiel, 2005;Tal, Bamberger & Morag, 2005). Bu süreçte öğretmenlere büyük görevler düşmektedir.…”
Section: Introductionunclassified
“…Por otra parte, Tal et al (2005) desarrollaron un estudio durante 3 años, teniendo como objeto principal las visitas escolares a cuatro Museos de Historia Natural, específicamente, la estructura de la visita, las explicaciones y cuestionamientos de los guías y la relación entre el docente y el guía. Desde esta investigación se logró reconocer que el patrón principal consistía en visitas guiadas y centradas en tareas orientadas a la actividad.…”
Section: Panorama De Las Investigaciones Desarrolladas En Torno a La unclassified